Assessing Trainees and Making Entrustment Decisions: On the Nature and Use of Entrustment-Supervision Scales. (November 2020) - ten Cate, Olle; Schwartz, Alan; Chen, H. Carrie
Abstract : Clinical teachers are continuously entrusting trainees with care responsibilities in health care settings. Entrustable professional activities employ entrustment decision making as an approach to assessment in the workplace. Various scales have been created to measure "entrustment, " all basically expressing the level or type of supervision a trainee requires for safe and high-quality care. However, some of these scales are only weakly related to the purpose of making decisions about the autonomy trainees will be granted. The authors aim to increase understanding about the nature, purpose, and practice of supervision scales aimed at entrustment. After arguing for entrustment as a component of workplace-based assessment, the distinction between ad hoc entrustment decisions (daily decisions in health care settings) and summative entrustment decisions (with a certifying nature) is clarified. Next, the noncontinuous nature of entrustment-supervision (ES) scales, as opposed to most workplace-based assessment scales, is explained. ES scales have ordinal, rather than interval, properties and focus on discrete decisions. Finally, some scales are retrospective ("how much supervision was provided?"), and others are prospective ("how much supervision will be needed in the near future?"). Although retrospective scales reflect observed behavior, prospective scales truly focus on entrustment and ask for more holistic judgment, as they include a broader evaluation and a risk estimation to enable a decision about increase of autonomy. The analysis concludes with a discussion about entrustment for unsupervised practice and supervision of others, as well as the program, context, and specialty specificity of scales.